Rosalyn Drexler - Who does she think she is? - Siegel, Katy 1966- (Gregory R. Miller & Co., 2016)
"Rosalyn Drexler has always moved between worlds. In the late 1950s and early '60s, she showed sculpture at New York's Reuben Gallery, a gathering place for artists like Allan Kaprow and Claes Oldenburg who combined installation and performance with traditional media. Drexler took part in Happenings at Reuben Gallery and at Judson Church (years after her own quasi-performance as a female wrestler, memorialized by Andy Warhol in the 1962 series Album of a Mat Queen). Drexler’s collages and large-format paintings of the 1960s open the category of Pop art to technology and politics in a way that feels contemporary today, crossing hard-edge painting with depictions of sex, violence, race and gender role-playing in film and media. Her writing also crosses high and low genres, comprising novels both experimental and popular, avant-garde theater and writing for television (including an Emmy-winning Lily Tomlin special). In addition to a comprehensive selection of Drexler's major paintings, Who Does She Think She Is? also recovers the artist's early sculptures, recently rediscovered and not exhibited since 1960. Documentation of Drexler's performances and theatrical work, photographs evoking her role in the downtown New York scene and a selection of her books and other archival materials present her work across multiple mediums, offering a comprehensive look at Drexler's varied career." -- Publisher's description
Published on the occasion of the exhibition held at the Rose Art Museum (February 12-June 5, 2016) and the Albright Knox Art Gallery (October 22, 2016-February 18, 2017). - Includes bibliographical references (pages 223-231) and index
Keywords: Drexler, Rosalyn -- 1926-; Zeichnung; Collage; Drexler, Rosalyn / Exhibitions / Drexler, Rosalyn / Catalogs; Ausstellungskatalog; Ausstellungskatalog -- Albright-Knox Art Gallery -- 22.10.2016-19.02.2017 -- Buffalo, NY; Ausstellungskatalog -- Rose Art Museum -- 12.02.2016-05.06.2016 -- Waltham, Mass.; Katalog